Ambulatory blood pressure monitoring in pregnancy induced hypertension - Arijit Biswas; Mahesh A. Choolani; Chinnayia Anandakumar; Sabaratnam Arulkumaran (Acta Obstetricia et Gynecologica Scandinavica)
Objective. To determine the role of ambulatory blood pressure monitoring in the diagnosis of pregnancy‐induced hypertension in women detected as hypertensive in the clinic by the conventional method. Design. An observational study of ambulatory blood pressure monitoring. Setting. A teaching hospital in Singapore. Methods. One hundred and twenty‐eight women between 28‐37 weeks of pregnancy diagnosed to have non‐proteinuric pregnancy‐induced hypertension in the clinic had 24 hours ambulatory blood pressure monitoring. The mean systolic and diastolic BP, systolic and diastolic ‘white coat effect’ and the diastolic load were the main parameters noted. Results. One hundred and twenty subjects had valid recordings. Only 46 (38.3%) were found to be truly hypertensive on ABP monitoring, using a mean diastolic pressure cut off of 85 mmHg. The ‘white‐coat effect’ was seen in both groups of women ‐ the hypertensives as well as the normotensives, although the magnitude of the white coat effect had poor correlation with the clinic diastolic BR A cut‐off value for diastolic load of 20 per cent was found to detect all hypertensives correctly (sensitivity 100%) with a modest false positive rate of 17.5 per cent. Conclusions. ‘White‐coat hypertension’ is common in pregnancy and ambulatory blood pressure monitoring would be helpful in identifying the true hypertensive without requiring unnecessary hospitalization.